Auditoría financiera y su relación con los resultados económicos de la cooperativa de transporte interprovincial Macuchi, cantón La Mana, año 2012 - Giler Navarrete, Ximena Yajaira (2015)
Once the investigation had been carried out could not verify that the Cooperative Macuchi interprovincial transport is governed by strict and rigorous way to the provisions established by the Law of cooperative, the Law of transit, transport and road safety as well as the Organic Statute of the entity; all of these regulations set out the basic guidelines of administrative management, financial and operational, as detailed in all of its components the set of rules for the proper functioning of this institution in the field of transit. In virtue of what, the Board of Directors of the Cooperative of interprovincial transport Macuchi must follow with the compliance of all those provisions and legal regulations, statutory regulations and in the organization, in such a way that guarantees the permanence of the entity over time. Well, in accordance to the financial indicators applied could not verify that the financial information of the Cooperative of interprovincial transport Macuchi presents an acceptable level of reliability; in this reason, the board of directors of the organization must apply to the counter the presentation of indicators and financial reports on a regular basis, so that the respective economic adjustments in case you need. Finally, once evaluated the internal controls that maintains the entity to safeguard their assets and submit the financial information with reasonableness, it was determined that the risk levels were established as follows: Risk inherent with a 25 per cent considered to be low, the risk of control was a 11 per cent and finally the risk of detection with a 20 per cent, which resulted in a 0.55 per cent of overall risk of audit. However, it is necessary that the general assembly of partners should ask the management to establish a permanent evaluation mechanism to the internal controls that maintains the entity to safeguard their assets and submit the financial information with the utmost reasonableness as possible.